2008
DOI: 10.1111/j.1365-3083.2007.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Analysis of Mycobacterium tuberculosis H37Rv Culture Filtrate Proteins

Abstract: Culture filtrates of Mycobacterium tuberculosis H37Rv highly enriched with secreted proteins were used to identify antigens recognized by a serum pool from tuberculosis patients. Two different approaches were used to separate the culture filtrate protein mixture: (i) proteins were fractionated according to their hydrophobicity using an HPLC‐C18 chromatography column followed by separation based on their molecular mass by SDS‐PAGE and subsequent immunoblotting or (ii) proteins were separated by two‐dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 33 publications
(41 reference statements)
1
60
0
2
Order By: Relevance
“…4; also, see Table S1 in the supplemental material). These proteins range from major secreted antigens encoded by Rv1174c (37), Rv1810 (38), Rv1926c (39), Rv1980c (38)(39)(40), Rv3004 (37), and Rv3312A (41) to integral membrane proteins (see Table S1). Notably, an L,D-transpeptidase, Ldt Mt4 , encoded by Rv0192 (24), is 4.4-fold more abundant in the cytoplasm of M12 than in that of the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
“…4; also, see Table S1 in the supplemental material). These proteins range from major secreted antigens encoded by Rv1174c (37), Rv1810 (38), Rv1926c (39), Rv1980c (38)(39)(40), Rv3004 (37), and Rv3312A (41) to integral membrane proteins (see Table S1). Notably, an L,D-transpeptidase, Ldt Mt4 , encoded by Rv0192 (24), is 4.4-fold more abundant in the cytoplasm of M12 than in that of the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
“…ESAT-6 and CFP-10 are the secretory antigens encoded by RD1 region genes which are deleted in M. bovis BCG but present in M. tuberculosis [18]. Humoral response to different components of a major secretory protein Ag85complex in tuberculosis has been reported [19][20][21]. Hence utility of these antigens in the diagnosis of TB has been envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Ag85A, Rv3881c, LAM, Ara 6-BSA and ESAT-6 may be useful for the serodiagnosis of pulmonary and bovine TB respectively [7][8][9][10][11]. Ag85A, ESAT-6 and TB10.4 are strongly recognized by T-cells isolated from TB patients and have been seen to induce a robust cell mediated immune response [7,12,13].…”
Section: Introductionmentioning
confidence: 99%